Genome sequence and description of Anaeromassilibacillus senegalensis gen. nov., sp. nov., isolated from the gut of patient with kwashiorkor. (May 2017) - Guilhot, E.; Alou, M.T.; Lagier, J.-C.; Labas, N.; Couderc, C.; Delerce, J.; Diallo, A.; Sokhna, C.; Fournier, P.-E.; Raoult, D.; Khelaifia, S.
Abstract: Using the culturomics strategy, a wide range of anaerobic bacteria was discovered including Anaeromassilibacillus senegalensis strain mt9 T (= CSUR P1511 = DSM 102954), isolated from the gut microbiota of a 1-year-old Senegalese patient with kwashiorkor. This Gram-negative strain is a strictly anaerobic, spore-forming rod motile by a polar flagellum. The 3 511 289 bp long genome of this strain contains 3046 protein-coding and 49 RNA genes, including 45 tRNA and four rRNA genes, and exhibits a G+C content of 52.94%. Here we describe the features of this organism, together with the complete genome sequence and annotation.